Penalty analysis is an efficient tool for food product development. Case study with lemonades. - Gere, Attila (Journal on Processing and Energy in Agriculture, 2023)
Although penalty analysis has been used for product development for many years, its application is less widespread. Penalty analysis provides a quick and easy way to identify those sensory attributes that significantly influence consumers’ preferences. The information provided helps food product developers to focus on key sensory attributes and with their improvement the overall product preference increases. The present paper focuses on the introduction of penalty analysis to the readers through an example of lemonades. Three prototypes of lemonades were tested with 30 consumers to identify the optimal level of sugar and lemon juice content that meets the need of the majority of the consumer group. Results suggest that with only three prototypes, the proper composition is easy to define.
Keywords: sensory analysis; consumer; nonparametric; product development